Frailty syndrome in institutionalized elderly: prevalence and associated factors - Melo,Elisa Moura de Albuquerque (2016)
To investigate the prevalence and the factors associated with frailty syndrome in institutionalized elderly, residents in the city of Recife/PE, a descriptive, cross-sectional, quantitative study was performed in nine public or philanthropic Homes for the Aged, between January and May 2013. We included 214 seniors, assuming as independent variables, the sociodemographic and health conditions, self-reported or obtained from elderly records, and the degree of elderly fragility, as dependent variable, assessed by Edmonton Fragility Scale. The mean age equaled to 76.42 ± 0.66 years (95%CI 75.12 – 77.71). We found a predominance of females (69.6%), unmarried (53.7%), with study time ranging from one to four years (54.4%). More frequently they referred perception of income (86.4%) up to one minimum salary (73.4%) and the residence time was less than a year to 29.4% of elderly. Regarding cognition, 79.4% of respondents were disapproved by significant errors. The frailty syndrome was identified in 70.1% of the elderly. All factors included in elderly frailty scale reached statistical significance, associated with increased frailty prevalence, as well as education, with a prevalence equal to 3.0 (95%CI 1.3 – 6.6) for its absence, and 2.5 (95%CI 1.2 – 5.3), for a four-year study. The absence of personal income increased at twice the prevalence (95%CI 1.0 – 4.0). In multivariate analysis, the factors that most contributed to the prevalence were impaired cognition, functional independence, self-evaluation of health, frequency of social support, perceived weight loss and feeling of sadness/depression.